Implantable Neurostimulation for Headache Disorders: Effect on Healthcare Utilization and Expenditures. Issue 3 (9th February 2016) - Farber, S. Harrison; Hatef, Jeffrey; Han, Jing L.; Marky, Andrew H.; Xie, Jichun; Huang, Kevin; Verla, Terence; Lokhnygina, Yuliya; Collins, Timothy A.; Lad, Shivanand P.
Abstract : Objectives: Chronic daily headache is a considerable source of morbidity for patients and also carries an enormous economic burden. Patients who fail standard medication regimens lack well‐defined therapies, and neurostimulation is an emerging option for these patients. The purpose of this study was to analyze the cost utility of implantable neurostimulation for treatment of headache. Methods: We utilized the Thompson Reuters Marketscan Data base to identify individuals diagnosed with headache disorders who underwent percutaneous neurostimulation. Healthcare expenditures for individuals who subsequently received permanent, surgically implanted neurostimulatory devices were compared to those who did not. Only individuals who sought implantable neurostimulation were included to account for headache severity. The cohorts were adjusted for comorbidity and prior headache‐related expenses. Costs were modeled longitudinally using a generalized estimating equation. Results: A total of 579 patients who underwent percutaneous trial of neurostimulation were included, of which 324 (55.96%) converted to permanent neurostimulation within one year. Unadjusted expenditures were greater for patients who underwent conversion to the permanent neurostimulation device, as expected. Costs grew at a lower rate for patients who converted to permanent device implantation. Cost neutrality for patients receiving the permanent device was reached in less than five years after the enrollment date. The mean cost of conversion to a permanent implantation was $18, 607.53 (SD $26, 441.34). Conclusions: Our study suggests that implantable neurostimulation reduces healthcare expenditures within a relatively short time period in patients with severe refractory headache.